1995
DOI: 10.1002/polb.1995.090330217
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in alternating polyketones studied by x‐ray diffraction and calorimetry

Abstract: Differential scanning calorimetry and high temperature x‐ray diffraction were used to study the perfectly alternating copolymer of ethene and carbon monoxide (polyketone; POKC2). It was found that oriented POK‐C2 fibers show a crystalline phase transition at a temperature between 110–125°C with a 10% change in crystalline density. At this temperature, the crystal structure reported recently (POK‐α) is transformed to a crystal structure that was reported in the past for room temperature imperfectly alternating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
89
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 12 publications
9
89
0
Order By: Relevance
“…The IR spectra show typical stretching absorptions of CO groups at 1695 cm −1 and of -CH 2 − groups at 2915 cm −1 . Table 1 shows some selected 1 H NMR e 13 C NMR signals and the assignments are in good agreement with the values reported in literature [34,35]. The LVN of a dilute polyketone solution was determined by using the Huggins relationship between the viscosity number and the polymer concentration by extrapolation to zero concentration [36].…”
Section: Polymers Characterizationsupporting
confidence: 83%
See 1 more Smart Citation
“…The IR spectra show typical stretching absorptions of CO groups at 1695 cm −1 and of -CH 2 − groups at 2915 cm −1 . Table 1 shows some selected 1 H NMR e 13 C NMR signals and the assignments are in good agreement with the values reported in literature [34,35]. The LVN of a dilute polyketone solution was determined by using the Huggins relationship between the viscosity number and the polymer concentration by extrapolation to zero concentration [36].…”
Section: Polymers Characterizationsupporting
confidence: 83%
“…This is because the ECO copolymer is a highly crystalline material with high melting point (T m ), whereas the terpolymers have lower melting points, making them more easily processable [13][14][15][16][17][18][19]. As matter of fact, the first commercialized PK, was the propene (P)-ethene-CO (PECO) terpolymer (trade name CARILON ® by Shell [20] and KETONEX ® by BP [21]).…”
Section: Introductionmentioning
confidence: 99%
“…2. From the comparison of the observed and the literature data for perfectly alternating ethene-CO (E-CO) copolymers, it can be concluded that the chains of EPEC 2 terpolymer crystallize in the distorted lattice close to the b-form of ethene-CO which is characteristic for copolymers with a low content of P-CO units [14][15][16] . The released specimen shows almost the same wide angle X-ray pattern in accordance with the earlier described irreversible mechanical behavior of the semicrystalline EPEC 2 sample.…”
Section: X-ray Investigationmentioning
confidence: 91%
“…The crystal structure of poly(ethene-alt-CO) in well-oriented fibers (a-structure) was determined by wide-angle X-ray scattering methods [64]. Klop et al showed that the a-form was dominant in the perfectly alternating copolymer at room temperature and that the phase transition from a to b was observed at 110-125 C [66]. The very dense packing is a result of the arrangement of the dipoles in the crystal lattice, giving rise to strong lateral forces between the polymer chains.…”
Section: Conformational Studies On the Optically Active Polyketonesmentioning
confidence: 99%